2023
DOI: 10.1080/14658011.2023.2231286
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of carbon-based rubber nanocomposites: A review

Abstract: Developing thermally conductive rubber nanocomposites for heat management is a difficult task for many applications, including tires. Even though rubber materials generally have poor thermal conductivity, the addition of various conductive fillers is required to prevent heat accumulation. However, high filler loading has a significant effect on the mechanical properties of the final product. In addition to the role of filler loading, structure, and morphology, various types of functionalization are required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…A hybrid filler system, encompassing thermally conductive fillers of varied sizes, shapes, or chemical properties, has been demonstrated to optimize distribution within the matrix and foster the creation of efficient thermal conduction pathways. For instance, in contrast to three-dimensional (3D) filler structures, one-dimensional (such as carbon nanotubes) and two-dimensional (2D) fillers with a high aspect ratio possess the capability to forge continuous, thermally conductive pathways within the polymer matrix, even when present in relatively low volume fractions [74][75][76][77][78][79][80]. Therefore, it can be concluded that improved distribution of MWCNTs in rubber matrix through high-torque micro-compounder facilitated a phenomenon known as the "dilution effect" arising from the reduction in interstitial gaps between adjacent filler particles as the filler content is increased.…”
Section: Electrical and Thermal Conductivity Test Resultsmentioning
confidence: 99%
“…A hybrid filler system, encompassing thermally conductive fillers of varied sizes, shapes, or chemical properties, has been demonstrated to optimize distribution within the matrix and foster the creation of efficient thermal conduction pathways. For instance, in contrast to three-dimensional (3D) filler structures, one-dimensional (such as carbon nanotubes) and two-dimensional (2D) fillers with a high aspect ratio possess the capability to forge continuous, thermally conductive pathways within the polymer matrix, even when present in relatively low volume fractions [74][75][76][77][78][79][80]. Therefore, it can be concluded that improved distribution of MWCNTs in rubber matrix through high-torque micro-compounder facilitated a phenomenon known as the "dilution effect" arising from the reduction in interstitial gaps between adjacent filler particles as the filler content is increased.…”
Section: Electrical and Thermal Conductivity Test Resultsmentioning
confidence: 99%
“…Finally, the swelling behavior of rubbers in biodiesel and IRM 903 was measured. Based on earlier studies, it was found that the addition of SWCNTs resulted in the improvement of tensile strength, modulus, hardness, and electrical conductivity of the blends, while the elongation at break was slightly reduced [ 31 , 32 , 33 , 34 ]. Previous studies have been conducted on the effect of SWCNTs on the mechanical and electrical conductivity properties of rubber.…”
Section: Introductionmentioning
confidence: 99%
“…The rubber industry has explored a wide range of additives and modifiers to optimize the behavior of these materials for their various applications, improving their respective properties and performance. For example, one of the most interesting applications described in the literature is the use of fillers to impart better mechanical properties, such as carbon black, silica, organoclays and graphene materials, among others [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%